Digestilidade in vitro do bagaço de cana-de-açúcar hidrolisado, submetido a diferentes tempos de estocagem e de adaptação ao bovino doador de fluido ruminal - deOliveira, M. D.; Kladt, FEK (Revista Sociedade Brasileira Zootecnia, 1997)
An experiment was conducted to study the in vitro digestibility of dry matter (IVDMD) and gross energy (IVGED) of hydrolyzed sugarcane bagasse with different storage times and two periods of adaptation of the bovine to the diet. A completely randomized design with four treatments and five replications was used. Treatments A,B,C, and D which corresponded to the times of 0, 15, 30, and 45 days of storage time period of the bagasse, respectively. Each treatment was studied at 7 and 45 after adaptation of the bovine ruminal donor to the diet. After 30 days storage, the bagasse IVDMD was inpaired for both 7 and 45 days of adaptation. Averages values of 25.8; 25.9; 23.1 and 23.3% were obtained for IVDMD with seven days of adaptation, and 25.04; 21.6; 12.5 and 11.4% with 45 days of adaptation for storage periods of 0; 15; 30 and 45 days, respectively. For IVGED, the averages obtained were 33.4; 27.8; 30.9; and 27.2% with seven days, and 30; 26.6; 20.6 and 14.5% with 45 days of adaptation for storage periods of 0, 15, 30 and 45 days, respectively.
In vitro digestibility of hydrolyzed sugar cane bagasse, submitted to different storage times and two periods of adaptation of the bovine ruminal fluid donor
Keywords: hydrolyzed bagasse; bovine; storage; ruminal fluid